Large Spin Hall Conductivity in Epitaxial Thin Films of Kagome Antiferromagnet Mn3Sn at Room Temperature. Issue 1 (14th November 2022) - Bangar, Himanshu; Khan, Kacho Imtiyaz Ali; Kumar, Akash; Chowdhury, Niru; Muduli, Prasanta Kumar; Muduli, Pranaba Kishor
Abstract: Mn3 Sn is a non‐collinear antiferromagnetic quantum material that exhibits a magnetic Weyl semimetallic state and has great potential for efficient memory devices. High‐quality epitaxial c ‐plane Mn3 Sn thin films have been grown on a sapphire substrate using a Ru seed layer. Using spin pumping induced inverse spin Hall effect measurements on c ‐plane epitaxial Mn3 Sn/Ni80 Fe20, spin‐diffusion length ( λ Mn 3 Sn λ _Mn_3Sn ), and spin Hall conductivity (σSH ) of Mn3 Sn thin films are measured: λ Mn 3 Sn = 0.42 ± 0.04 λ _Mn_3Sn=0.42± 0.04 nm and σ SH = − 702 ℏ / e Ω − 1 σ_SH=-702 /e Ω^-1 cm −1 . While λ Mn 3 Sn λ _Mn_3Sn is consistent with earlier studies, σSH is an order of magnitude higher and of the opposite sign. The behavior is explained on the basis of excess Mn, which shifts the Fermi level in these films, leading to the observed behavior. These findings demonstrate a technique for engineering σSH of Mn3 Sn films by employing Mn composition for functional spintronic devices. Abstract : Non‐collinear antiferromagnetic quantum materials have gained attention as alternative spin Hall materials for spin‐to‐charge conversion. This work presents direct measurement of spin Hall conductivity (σSH ) in high‐quality c ‐plane oriented Mn3 Sn thin films. The σSH of epitaxial Mn3 Sn thin films is found to be −702 ℏ e Ω − 1 e Ω ^-1 cm −1 . The demonstration of large σSH would accelerate the development of antiferromagnetic‐based spintronic devices.